Pregnant women, weight gain and Auriculotherapy: a protocol for a randomized controlled trial. - Rezvanimagham, Maliheh; Valiani, Mahboubeh; Ebrahimi, Elham (International Journal of Travel Medicine & Global Health, 2023)
Introduction: The demographic characteristics of women who become pregnant have changed dramatically over the past decade. Most women are overweight or obese during pregnancy, so the growing global trend of being overweight during pregnancy has been accompanied by a concomitant increase in pregnancy complications. This study will evaluate the effect of ear acupressure (auriculotherapy) on the weighting pattern of overweight women during pregnancy. Methods: This study will be a single-blind randomized clinical trial with two intervention and control groups. A total of 130 eligible pregnant women will be selected by a purposeful sampling method and then divided into two groups of intervention and control by a random blocking method with quadruple blocks. In the intervention group, two seeds were placed in the left ear on the metabolism and stomach points, while two seeds were placed in the right ear on the mouth and appetite points. Participants in the intervention group must press the seeds 6 times a day, preferably 20 minutes before a meal. The seeds will be changed twice a week (once every three days) by the researcher. The total duration of the study will last for 5 weeks. For the control group, instead of the real seed, the Vaccaria seedless label (waterproof cloth adhesive) will be placed by the researcher at the same points as the intervention group. Results: Primary results include weight gain during 5 weeks of intervention compared to baseline weight. Secondary results include weight gain at the end of the intervention, then 2 and 4 weeks after the intervention compared to baseline weight. Adverse events during treatment and follow-up periods, regardless of the relationship with the interventions, are documented, reported to the ethics committee, and treated with appropriate treatment. Conclusion: This study is expected to support the effect of ear acupressure on the weight gain status of overweight women during pregnancy.